Benign (BI-RADS 2) lesions in breast MRI. Issue 4 (April 2015) - Spick, C.; Szolar, D.H.M.; Tillich, M.; Reittner, P.; Preidler, K.W.; Baltzer, P.A.
<x xml:space="preserve">Abstract</x> Aim To assess the frequency of malignancy in lesions characterized as benign [Breast Imaging—Reporting and Data System (BI-RADS) 2] on breast MRI. Materials and methods In this institutional review board-approved retrospective single-centre study, 1265 consecutive patients (mean age 50±13 years), undergoing dynamic contrast-enhanced MRI (1.5 T) of the breast during a 6 year time period, were eligible. This study investigated the MRI characteristics and frequency of malignancy in 192 of these patients with breast lesions classified as BI-RADS 2. Examinations were read during clinical practice and classified according to the MRI BI-RADS lexicon. Based on the patient's and referring physician's preferences, lesions were either histopathologically verified or were subjected to both clinical and imaging follow-up of at least 2 years (range 2–9 years). Descriptive statistical metrics were calculated. Results According to the standard of reference, 0 of 192 (0%) lesions classified as BI-RADS 2 were malignant. Histopathology was available in 67 (34.9%) lesions and revealed benign findings exclusively. The remaining 125 (65.1%) lesions did not exhibit changes during the follow-up period and were, therefore, considered negative for malignancy. Conclusions The frequency of malignancy in breast lesions classified as BI-RADS 2 is zero. As a consequence, breast biopsies are unnecessary in these cases.